Application of atomic simulation for studying hydrogen embrittlement phenomena and mechanism in iron-based alloys. (29th May 2022) - Dong, Linshuo; Wang, Shuize; Wu, Guilin; Gao, Junheng; Zhou, Xiaoye; Wu, Hong-Hui; Mao, Xinping
Abstract: High-strength iron-based alloys serving in hydrogen-containing environments often faces a critical problem of hydrogen embrittlement, which involves intricate mechanisms across multiple lengths and time scales resulting in catastrophic consequences. It is challenging to track the evolution or/and nanoscale distribution of hydrogen atoms via experiments directly, whereas atomic simulation displays its great advantages in revealing the hydrogen-related behaviors and interaction mechanism. Most studies on hydrogen embrittlement mechanisms via atomic simulations focused on iron, as it is the matrix composition of steel. Herein, we summarize recent advances about applying atomic simulations, including density functional theory and molecular dynamics, in understanding the interaction between hydrogen atoms and various defects in iron-based alloys. Finally, some scientific issues and challenges in this field are discussed to provide insight for future researches. Graphical abstract: Image 1 Highlights: Atomic simulations are helpful to understand hydrogen embrittlement phenomena. The advantages and limitations of atomic simulations are discussed. The interaction between hydrogen and defects by atomic simulations is discussed. How to fill the gap between experiments and atomic simulation is discussed.